Implementasi Program Padat Karya Produksi Paving dalam Upaya Mengatasi Kemiskinan : Studi di Kelurahan Siwalankerto, Kecamatan Wonocolo, Kota Surabaya, Provinsi Jawa Timur - Divarelia Fernanda; Radjikan Radjikan; Muhammad Roisul Basyar (Konstitusi : Jurnal Hukum, Administrasi Publik, dan Ilmu Komunikasi, 2025)
The Padat Karya (Labor-Intensive) Program is one of the strategies implemented by the Surabaya City Government to reduce poverty through local economic empowerment. This study aims to analyze the implementation of the Paving Production Padat Karya Program in Siwalankerto Sub-District, Wonocolo District, Surabaya City. The research used a descriptive qualitative approach with data collected through observation, interviews, and documentation. The analysis was based on Van Meter and Van Horn’s policy implementation model, which includes six indicators: policy standards and objectives, resources, inter-organizational communication, characteristics of implementing agents, social-economic-political environment, and disposition of implementers. The findings indicate that the program has not been implemented optimally. There is a lack of measurable operational indicators, limited available resources, and ineffective inter-agency coordination. Moreover, the absence of a dedicated implementation unit and weak affirmative policy support have hindered the program's sustainability. Both implementers and participants tend to be passive due to the lack of tangible economic outcomes. The study recommends strengthening institutional frameworks, improving capacity, and developing affirmative market-based policies to ensure the program's sustainability.